Studies on Different Seed Treatments with Polymer and Chemicals on Longevity of Wheat (Triticum aestivum L.) Seeds Stored for 24 Months - Jyoti, Aparna; Dhiman, Karam Chand; Maurya, Chhote Lal; Divya,; Kanwar, Rajesh; Thakur, Anubhav (International Journal of Economic Plants, 2025)
The experiment was conducted during (January–December, 2021) at CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur, Himachal Pradesh, India to examine how seed treatments affect seed quality and to determine which one of the seed treatments is most efficacious in enhancing the longevity of seeds of wheat. The wheat variety (HPW 155) seeds were treated with nine various treatments containing polym., FC, IC, polym.-FC and polym.-IC combinations and a control total of ten treatments. The seeds were stored in HDPE (High-density polyethene) interwoven non-laminated bags after treatments. The seed quality attributes were evaluated at the interval of two months for the period of twelve months (25th–36th months). Amongst different seed treatments, seed coated with Polm.+vitavax 200 (containing thiram, 37.5% and carboxyl, 37.5%) @2.0 g kg-1 of seed (T6) was found superior for quality attributes viz., GP (88.33%), SG (17.86), SL (15.11 cm), SDW (10.42 mg), SVI- I (1335), SVI- II (920) and FE (69.00%) which was at par with Vitavax 200 (containing thiram, 37.5% and carboxyl, 37.5%) @2.0 g kg-1 seed (T5) at the completion of 36 months of storage in comparison to UC (T1) Hence, polymer in combination with vitavax or vitavax alone can also effectively prevent the fast deterioration of seed during the storage period as they maintain the seed quality parameters for a long duration of time.